The Role of the Village Government in Improving Human Resource Development in Padaherang Village, Padaherang District, Pangandaran Regency - Dede Agus Norma Rohiman; Regi Refian Garis; Neti Sunarti (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This research is motivated by the suboptimal role of the Padaherang Village government in providing equitable access to education and training for the community. Skills training such as culinary arts, sewing, or organic farming is still rare and limited to specific groups such as the Family Welfare Movement (PKK) or the Youth Organization (Karang Taruna). Non-formal learning programs that can reach all ages are also underdeveloped, for example, there are no evening classes for illiterate adults or group learning activities at the village hall. Furthermore, the community's use of technology has not been directed towards productive activities. Although many residents own Android phones, their use is limited to basic communication and entertainment. Training to improve digital literacy, such as promoting MSME products or accessing online services, has never been conducted. The purpose of this study is to analyze the role of the village government in human resource development. Using a qualitative descriptive method, the results show that of the five government roles according to P. Siagian's theory, the roles as stabilizer and innovator have not been optimally implemented. The main obstacles include limited funds, training personnel, internet infrastructure, and low community literacy. However, the role as a modernizer is beginning to be seen through the active involvement of residents. Efforts include collaborating with training institutions, submitting programs through village meetings, involving volunteers, and planning basic technology training for youth. The village government has also begun promoting the benefits of technology through community forums as part of its official work program.